Extreme trait GWAS (Et-GWAS): Unraveling rare variants in the 3,000 rice genome - Gnanapragasam, Niranjani; Prasanth, Vinukonda Vishnu; Sundaram, Krishna Tesman; Kumar, Ajay; Pahi, Bandana; Gurjar, Anoop; Venkateshwarlu, Challa; Kalia, Sanjay; Kumar, Arvind; Dixit, Shalabh; Kohli, Ajay; Singh, Uma Maheshwer; et al. (Life Science Alliance, 2024)
Identifying high-impact, rare genetic variants associated with specific traits is crucial for crop improvement. The 3,010 rice genome (3K RG) dataset offers a valuable resource for discovering genomic regions with potential applications in crop breeding. We used Extreme Trait GWAS (Et-GWAS), employing bulk pooling and allele frequency measurement to efficiently extract rare variants from the 3K RG. This innovative approach facilitates the detection of associations between genetic variants and target traits, concentrating and quantifying rare alleles. In our study, on grain yield under drought stress, Et-GWAS successfully identified five key genes (OsPP2C11, OsK5.2, OsIRO2, OsPEX1, and OsPWA1) known for enhancing yield under drought. In addition, we examined the overlap of our results with previously reported qDTY-QTLs and observed that OsUCH1 and OsUCH2 genes were located within qDTY2.2. We compared Et-GWAS with conventional GWAS, finding it effectively capturing most candidate genes associated with the target trait. Validation with resistant starch showed similar results. To enhance user-friendliness, we developed a GUI for Et-GWAS; https://et-gwas.shinyapps.io/Et-GWAS/.